Aerosol particles at a high‐altitude site on the Southeast Tibetan Plateau, China: Implications for pollution transport from South Asia. Issue 19 (4th October 2013) - Zhao, Zhuzi; Cao, Junji; Shen, Zhenxing; Xu, Baiqing; Zhu, Chongshu; Chen, L.‐W. Antony; Su, Xiaoli; Liu, Suixin; Han, Yongming; Wang, Gehui; Ho, Kinfai
Abstract [1] Bulk aerosol samples were collected from 16 July 2008 to 26 July 2009 at Lulang, a high‐altitude (>3300m above sea level) site on the southeast Tibetan Plateau (TP); objectives were to determine chemical characteristics of the aerosol and identify its major sources. We report aerosol (total suspended particulate, TSP) mass levels and the concentrations of selected elements, carbonaceous species, and water‐soluble inorganic ions. Significant buildup of aerosol mass and chemical species (organic carbon, element carbon, nitrate, and sulfate) occurred during the premonsoon, while lower concentrations were observed during the monsoon. Seasonal variations in aerosol and chemical species were driven by precipitation scavenging and atmospheric circulation. Two kinds of high‐aerosol episodes were observed: one was enriched with dust indicators (Fe and Ca2+), and the other was enhanced with organic and elemental carbon (OC and EC), SO42−, NO3−, and Fe. The TSP loadings during the latter were 3 to 6 times those on normal days. The greatest aerosol optical depths (National Centers for Environmental Protection/National Center for Atmospheric Research reanalysis) occurred upwind, in eastern India and Bangladesh, and trajectory analysis indicates that air pollutants were transported from the southwest. Northwesterly winds brought high levels of natural emissions (Fe, Ca2+) and low levels of pollutants (SO42−, NO3−, K+, and EC); this was consistent with high aerosol optical depths over the western deserts and Gobi. Our work provides evidence that both geological and pollution aerosols from surrounding regions impact the aerosol population of the TP.